Formation of biliodigestive anastomoses with the TiNi compression device - G. T. Dambaev; M. M. Solovyov; V. E. Gyunter; E. A. Avdoshina; O. A. Fatyushina; N. E. Kurtseitov; A. M. Fatyushina (Acta Biomedica Scientifica, 2018)
In our research, we evaluated the effectiveness of the device for the valve compression anastomoses formation in animals. The implant is made of the titanium nickelide alloy (TiNi) in the form of two loops of the TiNi wire. In the area of the bent turns, compression is not carried out, the tissue is not squeezed, and later the valve is formed in the zone of anastomosis. Twenty-six antireflux biliodigestive compression anastomoses on the small bowel have been created during the experiment. They include 13 choledochojejunostomies and 13 cholecystojejunostomies. We studied the terms of the compression devices failure, the mechanical and biological durability of these anastomoses, the primary permeability of anastomoses and carried out the microscopic examination of the compression suture. We proved that all valve compression anastomoses created with TiNi shape-memory implant have been mechanically and biologically tight. The compression devices were eliminated from the zones of anastomoses on the 7th-8th day after the surgery in all cases. The microscopic examination showed the insignificant development of sclerosis in the compression zone and full adaptation of all organ layers. The created valve reduced the reflux of intestinal contents that lessened the probability of development of acute and chronic cholangitis in the postoperative period. The use of the TiNi implant allows to carry out the operation twice quicker. Such anastomosis has high physical durability and low bacteriological permeability. The new way of the formation of valve biliodigestive compression anastomoses allows to create stronger and more reliable anastomoses and prevent the development of typical complications.